2003
DOI: 10.1063/1.1572965
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier mobility in doped semiconducting polymers

Abstract: An analytic model of the equilibrium hopping conductivity in a disordered organic semiconductor at large charge carrier densities is formulated. Calculated dependences of the equilibrium hopping mobility upon the carrier density are compared with recent experimental data obtained on doped poly(3-hexylthiophene) films. Doping is shown to create additional energy disorder due to potential fluctuations caused by the Coulomb field of randomly distributed dopant ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
160
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(170 citation statements)
references
References 9 publications
9
160
0
Order By: Relevance
“…As we will see below this makes the carrier occupancy function to follow Fermi-Dirac statistics. 31,33 In contrast to previous studies 17,22 the Fermi-Dirac function is not imposed a priori, but it arises naturally from the calculation instead.…”
Section: Random Walk Numerical Simulation For Hopping Transport Amentioning
confidence: 99%
See 1 more Smart Citation
“…As we will see below this makes the carrier occupancy function to follow Fermi-Dirac statistics. 31,33 In contrast to previous studies 17,22 the Fermi-Dirac function is not imposed a priori, but it arises naturally from the calculation instead.…”
Section: Random Walk Numerical Simulation For Hopping Transport Amentioning
confidence: 99%
“…In this case it has been shown that a particular level called the transport energy determines the dominant hopping events for carriers sitting in very deep states. [16][17][18][19][20][21] The existence of an effective transport level reduces the hopping transport to multiple trapping, with the transport energy playing the role of a mobility edge. The transport energy concept has been utilized to derive a theoretical expression for the diffusion coefficient of electrons hopping in an exponential distribution of localized states.…”
Section: Introductionmentioning
confidence: 99%
“…21 Therefore we adopt the approach where the electronic states are static, while the fast nuclear vibrations (phonons) around the conformation cause the transitions between these states, in line with the traditional view in disordered polymers. [8][9][10][11][12] Both intrachain and interchain hopping are therefore treated on equal footing. The polaronic relaxation of carrier states was not included since recent density functional theory calculations 22,23 have shown that polaron binding energy in long straight polythiophene chains is of the order of few meVs only, suggesting that it is irrelevant for transport.…”
mentioning
confidence: 99%
“…In the last several decades, transport through disordered organic systems, including conjugated polymers, was traditionally analyzed using the phenomenological models [8][9][10][11][12] which do not consider the nanoscale structure of the material and contain several fitting parameters. One would certainly like to improve upon this simple picture and get an insight into the microscopic processes in the material.…”
mentioning
confidence: 99%
“…By controlling the distance between hopping sites, carrier mobility can be adjusted [6]. At thermodynamic equilibrium, charge carriers mostly occupy the deep tail states of the density-of-states (DOS) distribution [7]. Carrier hopping occurs mostly via shallower states [8,9].…”
Section: Introductionmentioning
confidence: 99%